Effect of Curcuma Powder on Total Cholesterol Level in Blood Serum in Diet-induced Hypercholesterolemia in Male Rabbits (Journal of Hama University, 2021)
The research was performed on (24) male sexually mature domestic rabbits, with average body weight (1-1.2) kg, and (4-6) months aged, in order to study the effect of curcuma powder on the level of Total cholesterol in the blood serum of male rabbits exposed to hypercholesterolemia. The experimental animals were placed in the barn of the veterinary departments unit, for a period of (15) days in order to adapt, and then randomly divided into (4) groups, each group (6) rabbits.Hypercholesterolemia was induced in the first group (Positive witness), by providing a hypercholesterolemia diet cholesterol 1% for (7) days, and left without treatment until the end of the experiment period (28 days). In the second group, hypercholesterolemia was also induced by the same method, and then they were treatment with curcuma powder 250 mg / kg added to the diet, until the end of the experiment period (28 days). As for the third group, they were offered a diet containing cholesterol 1% and curcuma 250 mg / kg throughout the experiment period (28 days). While the fourth group: (Negative group), rabbits feeding on normal diet without any additives for 28 days.Blood samples were collected twice from experimental animals, the first sample was at the end of the first week, (on day 8), and the second sample was at the end of the experiment, (on day 28), and then the serum samples were taken to the biochemical tests to determine total cholesterol. The results showed significant decrease (P